Effect of Distributed Photovoltaic Generation on the Voltage Magnitude in a Self-Contained Power Supply System; IOP Conference Series: Materials Science and Engineering; Vol. 127 : Urgent Problems of Modern Mechanical Engineering - Lukutin B. V. Boris Vladimirovich; Shandarova E. B. Elena Borisovna; Makarova A. F.; Shvartsman I. B. (2016, 2016)
Title screen